Understanding nurses' educational needs in the global setting through stakeholder analysis and electronic polling systems - Della, Phillip; Michael, Rene; Tulloch, Alan (Cambridge Media, 2011)
This paper provides guidance to perioperative nurses on undertaking a stakeholder analysis using an electronic polling system, Turning Point, to conduct research where the aim of the research can range from determining the requirements for programme development, policy analysis or the implementation of a specific policy. To illustrate this method, an example of a study is provided that seeks to obtain the views of international senior nurses regarding the educational needs of the nurses in their country. Issues are outlined that require consideration when undertaking this approach, including the advantages of the use of qualitative and quantitative data collection methods for estimating stakeholder positions.